No Individual Creativity, No Organizational Innovation - John Francis Hulpke (Journal of Innovation in Business and Economics, 2019)
Innovation is important. Creativity is a necessary prelude to innovation. Academics and professionals need to pay more attention to creativity. One reason for inadequate innovation is the lack of attention to creativity. A related issue appears to be systematic stifling of creativity. Business schools should be preparing tomorrow’s leaders for an exciting, stimulating, challenging and changing future. Too often universities train people to approach questions by looking at what has been done in the past. One confounding issue has to do with possible lack of clarity about terminology. Some confuse the two terms “innovation” and “creativity.” They are not the same although some use the terms interchangeably. This leads to possible confusion regarding “levels of analysis.” Creativity is an individual level factor. The term innovation is best applied at an organizational level of analysis. To foster and encourage organizational innovation, a recommended first step would be to encourage individual creativity.